Self-diffusion in granular gases: Green-Kubo versus Chapman-Enskog - Brilliantov, Nikolai V.; Pöschel, Thorsten (Chaos, 2005)
We study the diffusion of tracers (self-diffusion) in a homogeneously cooling gas of dissipative particles, using the Green-Kubo relation and the Chapman-Enskog approach. The dissipative particle collisions are described by the coefficient of restitution ε which for realistic material properties depends on the impact velocity. First, we consider self-diffusion using a constant coefficient of restitution, ε=const, as frequently used to simplify the analysis. Second, self-diffusion is studied for a simplified (stepwise) dependence of ε on the impact velocity. Finally, diffusion is considered for gases of realistic viscoelastic particles. We find that for ε=const both methods lead to the same result for the self-diffusion coefficient. For the case of impact-velocity dependent coefficients of restitution, the Green-Kubo method is, however, either restrictive or too complicated for practical application, therefore we compute the diffusion coefficient using the Chapman-Enskog method. We conclude that in application to granular gases, the Chapman-Enskog approach is preferable for deriving kinetic coefficients. © 2005 American Institute of Physics.